Novel inflammatory cell infiltration scoring system to investigate healthy and footrot affected ovine interdigital skin - Michael Agbaje; Catrin S. Rutland; Grazieli Maboni; Adam Blanchard; Melissa Bexon; Ceri Stewart; Michael A. Jones; Sabine Totemeyer (PeerJ, 2018)
Ovine footrot is a degenerative disease of sheep feet leading to the separation of hoof-horn from the underlying skin and lameness. This study quantitatively examined histological features of the ovine interdigital skin as well as their relationship with pro-inflammatory cytokine (IL-1β) and virulent Dichelobacter nodosus in footrot. From 55 healthy and 30 footrot ovine feet, parallel biopsies (one fixed for histology) were collected post-slaughter and analysed for lesions and histopathological analysis using haematoxylin and eosin and Periodic Acid-Schiff. Histological lesions were similar in both conditions while inflammatory scores mirror IL-1β expression levels. Increased inflammatory score corresponded with high virulent D. nodosus load and was significant (p < 0.0001) in footrot feet with an inflammatory score of 3 compared to scores 1 and 2. In addition, in contrast to healthy tissues, localisation of eubacterial load extended beyond follicular depths in footrot samples. The novel inflammatory cell infiltration scoring system in this study may be used to grade inflammatory response in the ovine feet and demonstrated an association between severity of inflammatory response and increased virulent D. nodosus load.